2017
DOI: 10.1016/j.appet.2017.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Lost in processing? Perceived healthfulness, taste and caloric content of whole and processed organic food

Abstract: The "organic" claim explicitly informs consumers about the food production method. Yet, based on this claim, people often infer unrelated food attributes. The current research examined whether the perceived advantage of organic over conventional food generalizes across different organic food types. Compared to whole organic foods, processed organic foods are less available, familiar and prototypical of the organic food category. In two studies (combined N = 258) we investigated how both organic foods types wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
78
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 73 publications
(105 reference statements)
4
78
0
1
Order By: Relevance
“…The paper by Prada et al (2017) found out that respondents perceive original unprocessed organic products as healthier, tastier, and more environmentally friendly than conventional food; however, the difference was not so significant with regard to organic food made from organic produce. We have considered organic food as a whole and we have found out that only a small proportion of respondents consider organic food to be tastier, while a significant number of them appreciate chemical-free environmentally friendly farming.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The paper by Prada et al (2017) found out that respondents perceive original unprocessed organic products as healthier, tastier, and more environmentally friendly than conventional food; however, the difference was not so significant with regard to organic food made from organic produce. We have considered organic food as a whole and we have found out that only a small proportion of respondents consider organic food to be tastier, while a significant number of them appreciate chemical-free environmentally friendly farming.…”
Section: Discussionmentioning
confidence: 93%
“…Our paper deals with this issue as well -we have been asking our respondents if they consider organic food to be healthier than regular food. The paper by Prada et al (2017) focused on different perception of organic product characteristics and regular traditional food characteristics as well as on the influence of various environmental messages contained in the media on such perception. This influence often represents the cause of distorted organic food quality perception based on irrelevant attributes.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, an "eco-friendly" or "organic" claim can lure people into believing it is healthier than an alternative, when this may not be true [48]. Consumers can infer proprieties that are unrelated to the production method, perceiving organic foods as healthier, tastier, and less caloric than those produced conventionally [49]. Perceived healthfulness of a food product and use of food labeling, in turn, influences food intake [50].…”
Section: Discussionmentioning
confidence: 99%
“…Packaged products as well as entail visual cues indicating both healthiness and tastiness. For example, cues related to naturalness have been found to signal good taste as well as superior healthiness to consumers (Lunardo & Saintives, ; Prada, Garrido, & Rodrigues, ). Another visual cue indicating both a product's healthiness and tastiness is the attractiveness of the package design.…”
Section: Introductionmentioning
confidence: 99%